An Analytical Study for Early Diagnosis and Treatment of Infants & Children Suffering From Congenital Hypothyroidism in China - Fuyong Jiao; Jianping Chen; Juan Liu; Ting Li; Fangting Liu (International Journal of Clinical Endocrinology and Metabolism - Peertechz Publications, 2015)
Objective: To study the clinical and laboratory characteristics of children suffering from congenital hypothyroidism in China. Method: 455 cases of congenital hypothyroidism infants were collected from 5 articles were published in 4 china medical journals. Different screening methods were adopted, like enzyme immunoassay assay and filter paper dried blood biotin-avidin enzyme notation to test TSH, FT3、FT. All the collected children treated by oral thyroxin tablets for long period and regular follow-up was done. Clinical follow up for any signs of hypothyroidism and also detection of I.Q of those children. Results: Markedly effective group: IQ >70%, height, constipation, lethargy, abdominal distension, jaundice and other symptoms and signs were improved after treatment. Effective group: IQ: 30%-70%, height, constipation, lethargy, abdominal distension, jaundice and other symptoms and signs were improved after treatment. Poor effective group: 0-30% IQ, while other signs and symptoms not much improved. Laboratory testing revealed au thyroid along with oral treatment of thyroxin in regular time and dose. Conclusion: Congenital hypothyroidism is a preventable disease if early diagnosis and treatment was done.